Initial lessons learned during a remote drug court evaluation during the COVID-19 pandemic - Hartsell, Elizabeth (Journal of crime and justice, 2022)
The COVID-19 pandemic has significantly changed how the justice system and its research partners can do their work. We were working with the Marion County Diversion Drug Court doing preliminary observations and developing a collaborative grant proposal to implement services and evaluate the program when the court was forced to move entirely online using Zoom due to the COVID-19 pandemic. This paper discusses how the transition to Zoom changed the evaluation of the drug court and service delivery. While we expected to conduct in-person focus groups and interviews with the court team and participants, as well as in-person observations of team meetings and court, these were not possible from March 2020 to June 2021 (in person court resumed in July 2021). Consequently, we adapted the now-funded, ongoing evaluation plan to conduct observations, interviews, and coding via Zoom and Qualtrics. We discuss the strengths, limitations, and early lessons learned from this endeavor. We also report initial findings on how COVID-19 affected service delivery and explore the possible implications of online drug court beyond the pandemic.